Environmental Monitoring of a Sanitary Landfill Project of Municipal Solid Waste for a Cluster of Villages in Lattakia - Ibrahim, Kinan (Latakia University Journal -Engineering Sciences Series, 2025)
Environmental monitoring is one of the most important tools for integrated management of municipal solid waste landfill sites. It allows the prediction of environmental impacts resulting from the operation of landfill sites according to environmental standards. Safe disposal of municipal solid waste is one of the most important challenges facing modern societies, especially since the amount of solid waste generated daily is increasing as a result of increasing population growth and high rates of solid waste production per capita. There is a number of methods commonly used to dispose of municipal solid waste, and their economic costs which vary depending on the method used and environmental requirements and conditions. The unregulated disposal of municipal solid waste leads to many environmental and health risks, including air, soil, surface and groundwater pollution, as well as multiple economic and social problems. This study aims to describe the systematic method for establishing a sanitary landfill for solid municipal waste generated by a cluster of villages in Lattakia with a population of approximately 25 thousand people. The study reviews the description of a sanitary landfill project for solid municipal waste in Al-Bahlouliya site. It also reviews an important part of the environmental impact assessment process for projects, which are related to identifying environmental indicators and developing a program and action plan for environmental monitoring to establish and operate a systematic sanitary landfill for solid municipal waste, taking into account the post-closure phase and subsequent use purposes.